GROWTH AND SURFACE PROPERTIES OF APATITE - Rakovan J. (My University, 2002)
The surface defines the interface between a mineral and its surroundings. In a dynamic context, reactions that occur between apatites and the environments in which they exist take place at or through their surfaces. This includes, but is not restricted to, crystal growth, dissolution, and surface-mediated reactions such as sorption, surface complexation, and catalysis (Hochella and White 1990). Because this interface is partly defined by the nature of the environment around the crystal, the properties, structure and chemistry of the crystal surface are always different than those of the bulk, and can be quite varied depending on the environment. For example, the crystal surface of apatite may have very different characteristics in contact with an aqueous solution as opposed to a polymerized silicate melt. Understanding the behavior of apatite surfaces is important on both the local and global scale. Apatite-water interactions can influence global biogeochemical systems such as the phosphorus cycle and the fate and transport of trace elements in Earth surface environments. The rapidly growing integration of surface science with the geological sciences is due to the realization that mineral surfaces are of great importance in a wide variety of natural processes. In order to understand the role of mineral surfaces on a global scale we must first understand the details of their structure and the interactions that take place on those surfaces at the atomic scale. This chapter provides a review of the nature of the apatite surface, particularly as it exists in contact with aqueous solutions, and the processes involved in apatite crystal growth. ### Morphology In igneous, metamorphic and hydrothermal systems apatite is most often found as euhedral to subhedral hexagonal crystals. The habit is usually prismatic, elongate along [001], or tabular, although equant crystals are not uncommon (Fig. 1⇓). The most common forms are {100}, {001}, …